Natural resources management in relation to jute and allied fibre crops - Saha, A R; Majumdar, B; Chowdhury, H; Maitra, D N; Saha, S (Indian Farming, 2015)
A large amount of nutrients are exhausted from soil every year by several crops under intensive cropping system particularly with high-yielding varieties. Annually India is depleting about 25 mt of nutrients through various crops. About 14 mt nutrients are replenished in the form of fertilizers and manures, thus leaving a negative balance of 11 mt. This continuous nutrient imbalance is a matter of concern in respect of future food and fibre need of our country. Therefore, we have to use the available nutrient resources more efficiently to maintain / increase the productivity in a sustainable manner.